REALISM AS GENETICS-TYPOLOGICAL PROBLEM - Golod, R. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In the article the history theoretical features of realism are considered as literary direction. View-philosophical ground is analyzed, basic stages of development that poetical dominants of realistic art.